Junior High School Teacher and Students’ Perspective on Actual Performance in Descriptive Text Writing: A Mixed Method Study - Firda Maghfiroh; Ahmad Munir (Universitas Galuh, 2026)
Writing descriptive text is an important skill in English learning at the junior high school level because it requires the ability to develop ideas, organize paragraphs, and use linguistic elements. Previous studies have mainly focused on students’ writing difficulties or learning strategies and rarely examined both teacher and student perceptions in relation to students’ actual writing performance. This study aims to explore teacher and student perceptions of students' actual performance in writing descriptive text and analyze the relationship between perceptions and actual writing performance. This study used a mixed-method approach combining descriptive qualitative and correlational quantitative approaches. The subjects consisted of one English teacher and 20 seventh-grade students. Data were collected through self-assessment questionnaires, semi-structured interviews, and document analysis of student writing. The results showed that teachers assessed students as having basic skills in developing ideas and content, but still experienced difficulties in vocabulary, grammar, paragraph organization, and writing mechanics. Students showed positive perceptions of writing motivation, but acknowledged linguistic difficulties. Correlation analysis showed a weak and negative relationship between students' perceptions and actual writing performance. The study indicated a gap between perceptions and actual performance and low metacognitive awareness of students. Therefore, explicit feedback, structured assessment, and strengthening of metacognitive awareness are needed in teaching descriptive text writing.